PENERAPAN METODE DEMONSTRASI DAN MEDIA FILM UNTUK MENINGKATKAN KEAKTIFAN DALAMPEMBELAJARAN DAN PRESTASI BELAJAR SISTEM REM - Agus Eka Saputra; Slamet Priyanto (Universitas Sarjanawiyata Tamansiswa, 2016)
This research aims: (1) to enhance students’ learning achievement in the subject of brake system class XI TKRA SMK Muhammadiyah 2 Sleman and (2) to improve students’ learning activeness in the subject of brake system class XI TKR A SMK Muhammadiyah 2 Sleman in the 2015/2016 academic year.This study is classroom action research done in 3 cycles which each cycle held in 4 stages, namely: planning, implementing, observation and reflection. This research was done in SMK Muhammadiyah 2 Sleman class XI TKR A in the 2015/2016 academic year with 40 students as the subjects. The data were collected using test, observation and documentation. The data were analyzed using descriptive quantitative technique.The results indicate that the implementation of demonstration method and film media shows the enhancement of learning achievement and activeness in the students of class XI TKR A SMK Muhammadiyah 2 Sleman on the subject of brake system in every cycle. It is shown by the improvement of students’ learning achievement test in cycle I which pre-test average value is 60.37 while post-test average value is 69.75. Thus, students’ learning achievement increases 9.38. In cycle II, it is obtained that the pre-test average value is 62.62 while the post-test average value is 75.25. Therefore, students’ learning achievement increases 12.63. In cycle III, the pre-test average value is 65.25 and the post-test average value is 82.75. Moreover, students’ learning activeness in the cycle I 42% increases 26% in the cycle II into 68 % and improves 19.50% in the cycle III to 87.50 %. Based on the above results, it can be concluded that the implementation of demonstration method and film media are able to improve students’ learning achievement and activeness on the subject of brake system class XI TKR A SMK Muhammadiyah 2 Sleman in the 2015/2016 academic year.